One-pot flash combustion synthesis of Fe@NiO nanocomposites for supercapacitor applications. Issue 7 (1st April 2021) - Khan, Aslam; Shkir, Mohd; Ansari, Sajid Ali; Parveen, Nazish; AlFaify, S.; El-Toni, Ahmed Mohamed; Gupta, Ravindra Kumar; Adil, Syed Farooq
Abstract: The authors report on the synthesis of Fe–NiO nanoparticles (Fe–NiO NPs) with a spherical shape via facile flash combustion synthesis. A structural test shows cubic formations of Fe–NiO NPs in all Fe concentrations. A reduction in crystallite size was observed with increasing Fe content from 27 nm to 12 nm. A vibrational study also indicates a cubic Fe–NiO NPs structure. However, slight shifts in peak positions were observed during Fe doping in NiO. The existence of Fe in NiO product was confirmed using energy dispersive X-ray (EDX) analysis, and its homogeneity in the final products was observed in scanning electron microscopy (SEM) e-mapping images. An X‐ray photoelectron spectroscopy (XPS) study was also carried out to confirm the incorporation of Fe in NiO matrix. A field-emission scanning electron microscopy (FESEM) study showed the formation of spherical nanoparticles in all Fe–NiO NPs samples. However, it was noted that the grain size reduced with increasing Fe content, which is in agreement with the X-ray diffraction (XRD) results. Transmission electron microscopy (TEM) and high-resolution TEM (HRTEM) with a selected area electron diffraction (SAED) curve indicate very low-dimension NP formation from NiO. An optical test was performed based on the Kubelka-Munk theory along with an estimation of energy gas, which showed an increase of 3.5–3.75 eV with Fe content doping in NiO. Furthermore, the possibility of applying spherical Fe–NiO NPs as an electrode material was also assessed in a three-electrode assembly cell, and the results show that the NiO doped with 5% of Fe exhibited superior capacitance performance (F4, 297.67 F g -1 ) compared to the other samples. Graphical abstract: Image 1 Highlights: High-quality Fe@NiO NPs are synthesized by one pot flash combustion route for the first time. XRD, Raman and XPS analyses approves the synthesis of monophasic NiO with Fe doping. A remarkable reduction in crystallite size was noticed from 27 to 12 nm. Enhancement in energy gap was noticed from 3.5 eV for pure to 3.76 eV for the 5.0 wt% sample. Among the entire electrodes, the 5% Fe@NiO delivered highest capacitance values.